Promotional effect of Ca doping on Bi2Fe4O9 as peroxymonosulfate activator for gatifloxacin removal. (November 2022) - Koo, Pooi-Ling; Choong, Zheng-Yi; Gasim, Mohamed Faisal; Khoerunnisa, Fitri; Jaafar, Nur Farhana; Saputra, Edy; Oh, Wen-Da
Abstract: A series of Ca-doped bismuth ferrite was prepared at various %w/w of Ca via a facile hydrothermal method to obtain Bi2X Ca2(1-X) Fe4 O9 (denoted as BFOCa-X, where X = 1, 0.95, 0.90, 0.80, 0.50). The BFOCa-X catalysts were characterized, and the results showed that they consist of pure phase BFO with nanosheet-like morphology. The as-prepared BFOCa-X catalysts were used as peroxymonosulfate (PMS) activator for gatifloxacin (GAT) removal. It was found that the catalytic activity decreased in the following order: BFOCa-0.8 (90.2% GAT removal efficiency in 45 min, k app  = 0.084 min −1 )>BFOCa-0.95 > BFOCa-0.9 > BFOCa-0.5 > BFO indicating that BFOCa-0.8 has the optimized active sites for catalysis. The Ca dopant contributed to the increased oxygen vacancies and surface hydroxyl groups, promoting the catalytic PMS activation process. The k app value increased gradually with increasing catalyst loading and PMS dosage while pH 9 presented the highest GAT removal rate. The GAT degradation rate was inhibited by PO4 3 ˉ, humic acid and NH4 + but promoted in the presence of Clˉ, NO3 ˉ and HCO3 ˉ. It was also found that the GAT can undergo several degradation pathways in the catalytic PMS system, which eventually mineralized into innocuous compounds. The dominant reactive oxygen species (ROS) were identified using chemical scavengers, revealing that SO4 ˉ, 1 O2 and OH contributed significantly to GAT degradation. Based on the XPS study, PMS was activated by the Fe 2+ /Fe 3+ redox cycling and oxygen vacancies to produce SO4 ˉ/ OH and 1 O2, respectively. Overall, the BFOCa-0.8 also showed excellent reusability up to at least 4 cycles with low Bi and Fe leaching (<7 and 62 μg L −1, respectively), indicating that it has promising potential for application as PMS activator for antibiotics removal. Graphical abstract: Image 1 Highlights: Ca-doped bismuth ferrite (BFOCa) was prepared hydrothermally and characterized. Ca doping induced the formation of oxygen vacancies in BFO to promote catalytic activity. BFOCa can effectively activate peroxymonosulfate (PMS) to degrade gatifloxacin (GAT). BFOCa activated PMS to produce SO4 . ˉ, 1 O2 and OH for GAT degradation. The degradation pathways of GAT were proposed based on the intermediates identified.